Selective Laser Melting of Free-Assembled Stainless Steel 316L Hinges: Optimization of Volumetric Laser Energy Density and Joint Clearance - Cho-Pei Jiang; Alvian Toto Wibisono; Shun-Hsien Wang; Tim Pasang; Maziar Ramezani (Metals, 2022)
Selective laser melting technology is one of the metal additive manufacturing technologies that can convert metal powder to complex parts without the assembly process. This study aims to optimize the volumetric laser energy density for printing 3D metal objects with hinges geometry. The material is stainless steel 316L powder. The volumetric laser energy densities ranging from 4.1 J/mm3 to 119.1 J/mm3 are applied to fabricate 3D free-assembled hinges with various clearances of 0.38 mm, 0.39 mm, 0.40 mm, and 0.41 mm and investigate the relationship between volumetric laser energy density and clearance. A multibody model, consisting of nine segments with eight hinges, is proposed to be printed with the optimized volumetric laser energy density. The optical microscope and the hardness test are performed to observe the porosity and hardness property of the SLMed object. The result shows that laser energy densities between 105.5 J/mm3 and 119.1 J/mm3 can produce the high densification of SLMed objects with a porosity defect of 0.24% to 0.20% and hardness in the range of 207 HV to 215 HV. The optimization of laser energy densities is in the range of 105.5 J/mm3 to 119.1 J/mm3, which can be used to fabricate the movable hinges with a minimum clearance size of 0.41 mm. The proposed dinosaur object is printed successfully and all joints are rotatable.